A Hermeneutic Analysis on ISAK 35: Habermas Perspective - Enrico Paul Anggiat Panjaitan; Syarifuddin Syarifuddin; Arifuddin Mannan (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2026)
Nonprofit-oriented entities play a critical role in providing social, educational, religious, and humanitarian services, yet face growing demands for transparent and accountable financial reporting. This study examines Interpretation of Financial Accounting Standards (ISAK) 35 on the Presentation of Financial Statements of Nonprofit-Oriented Entities through the lens of Jurgen Habermas’s critical hermeneutics. Employing a qualitative approach within an interpretive-critical paradigm, the study analyzes ISAK 35 as a normative accounting text to uncover the meanings, interests, and potential communicative distortions embedded within the standard. The primary data consist of the Exposure Draft of ISAK 35 and supporting documents, including the Conceptual Framework for Financial Reporting and relevant Indonesian Financial Accounting Standards (PSAK), collected through document analysis. Drawing on legitimacy theory and entity theory, the findings indicate that ISAK 35 functions not only as a technical guideline for financial reporting but also as a formal instrument of legitimacy for nonprofit organizations. The separation of net assets with and without restrictions reflects the application of entity theory and aims to enhance transparency and accountability. However, from a critical perspective, the study finds that the emphasis on compliance and technical presentation may reinforce instrumental rationality, potentially limiting dialogical communication between nonprofit entities and their stakeholders, particularly in organizations lacking adequate accounting competence. This study contributes to critical accounting literature by highlighting the need to balance standardization with substantive public accountability and communicative rationality in nonprofit financial reporting.